Refresher Training Workshop on Feeds and Forage for Dairy Development - Mekonnen, Kindu; Gebreyes, Million; Bezabih, Melkamu; Assefa, Getnet; Mesfin, Hailemariam (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
Report on Refresher Training Workshop on Feeds and Forage for Dairy Development 27-28 March 2023| Addis Ababa, Ethiopia